Analysis of Errors in English Narrative Writing of STIE Port Numbay Students - Terweline Tapilatu (LADU: Journal of Languages and Education, 2023)
Background: The making of errors in second language acquisition, especially in writing, is natural, but the errors should not be ignored and need to be treated properly. Purpose: The purposes of this descriptive research are to identify the types of errors occured in the narrative writing of first-year students at STIE Port Numbay in Jayapura, explain the causes of the errors and the strategies applied to correct them and to prevent them from happening in the future. Design and methods: This research is a descriptive qualitative one that uses the content analysis method. The data were taken from 20 narrative writings about daily activities made by 20 first-year students of STIE Port Numbay in Jayapura who major in Development Economics and took the English 1 course in the Odd Semester of the 2020/2021 Academic Year. Results: The findings revealed that there are 9 types of error occured i.e. omission, addition, misselection, misordering, blending, misformations, misspellings, sentence errors and semantic errors in lexis. The errors are caused by interference of the first language or interlingual, inadequate mastery of the target language rules or intralingual and limited vocabulary. The strategies for the error correction are direct feedback and exposing the target language use by its native speakers so that the learners can compare it with their own L2 use. To prevent the same errors, the instructor can improve the learners' mastery of the target language rules by using creative and varied teaching methods and materials as well as encouraging the learners to develop the habit of reading English texts in order to improve their vocabulary and to obtain input about the use of English in writing. Keywords: Error analysis, interlingual, intralingual